Prevención del abuso infantil - Carrasco Oliva, Iris Isabel (2018)
Sexual Abuse is a problem that we face as a society and that definitely worries teachers and parents. Despite the concern that exists, it is a problem that has been kept hidden and which is not talked about much. But currently, psychologists and specialists consider it very important that, in order to prevent and combat this problem, talk and manage it properly. Sexual abuse of minors is a problem that has only recently begun to be studied. After centuries of silence, although sexual abuse has always occurred (although we do not know well in what proportion), in which science has not dealt with this problem, this topic began to be discussed at the beginning of the Last century. The first to acknowledge that the abuses were frequent was Freud but, perhaps because of the social pressure he suffered in revealing this problem, he ended up defending that in most cases these were not real, but fantasized by the children themselves. Aspect that is currently rejected by professionals who work with abuse. Children and adolescents need to be prevented from this constant danger that threatens child abuse and we are the teachers who can give the knowledge to prevent such abuse to the body that damages the soul of our children and affects their emotional stability